Problem diagnostik seorang penderita endokarditis infektif dengan komplikasi perdarahan intrakranial: Sebuah laporan kasus - Franky Simarmata; Ida Bagus Aditya Nugraha; I Wayan Wita; Dwijo Anargha Sindhughosa (DiscoverSys Inc., 2021)
Introduction: Infective Endocarditis (IE) is a disease frequently affecting heart valves. The diagnosis is relatively simple, however it could be difficult in unspecific symptoms. Intracranial complications of patients with IE rarely happen.Case: The case was a 64 years-old male with sudden decrease of consciousness 12 hours prior to admission and diagnosed as a hemorrhagic stroke. He had a history of heavy smoking for about 10 years. Infective Endocarditis (IE) was diagnosed by Duke Criteria, and from this patient we found the vegetation at mitral valve with diameter 1.09 x 0.73 cm. Treatment for the patient is antibiotic according to sensitivity test of blood culture. The patient was discharged with improvement of condition. However, in approximately three months after discharge, the patient got hospitalized again due to the same condition and passed away.Conclusion: Infective endocarditis is a relatively rare disease. In our case we had a definite IE patient with a spectrum of neurological events complicating this disease. The presence of cerebral hemorrhage complications makes the patient's prognosis worse. Pendahuluan: Endokarditis Infektif (IE) merupakan penyakit yang umumnya menyerang katup jantung. Diagnosis pada umumnya relatif sederhana, namun dapat menjadi sulit gejala yang ditemukan tidak spesifik. Komplikasi intrakranial pasien dengan IE jarang terjadi.Laporan Kasus: Seorang laki-laki 64 tahun dengan penurunan kesadaran mendadak 12 jam sebelum masuk rumah sakit (MRS) dan didiagnosis sebagai stroke hemoragik. Pasien memiliki riwayat perokok berat selama kurang lebih 10 tahun. Endokarditis infektif (IE) di diagnosis dengan kriteria Duke, dan dari pasien ini ditemukan vegetasi pada katup mitral dengan diameter 1,09 x 0,73 cm. Pengobatan untuk pasien adalah antibiotik berdasarkan uji sensitivitas kultur darah. Pasien dipulangkan dengan kondisi perbaikan. Namun, sekitar tiga bulan setelah keluar, pasien kembali dirawat di rumah sakit karena kondisi yang sama dan meninggal dunia.Simpulan: Endokarditis infektif merupakan penyakit yang relatif jarang. Dalam laporan kasus ini, pasien dengan spektrum kejadian neurologis yang menyulitkan penyakit IE. Adanya komplikasi perdarahan otak membuat prognosis pasien semakin buruk.